Spider silk-bone sialoprotein fusion proteins for bone tissue engineering - Gomes, Sílvia C. (2011)
The remarkable mechanical characteristics of the spider silk protein major ampullate spidroin protein suggest this polymer as a promising biomaterial to consider for the fabrication of scaffolds for bone regeneration. Herein, a new functionalized spider silk-bone sialoprotein fusion protein was designed, cloned, expressed, purified and the osteogenic activity studied. Bone sialoprotein (BSP) is a multidomain protein with the ability to induce cell attachment and differentiation and the deposition of calcium phosphates (CaP). Attenuated Total Reflection Fourier Transform Infrared (ATR-FTIR) was used to assess the secondary structure of the fusion protein. In vitro mineralization studies demonstrated that this new fusion protein with BSP retained the ability to induce the deposition of CaP. Studies in vitro indicated that human mesenchymal stem cells had significant improvement towards osteogenic outcomes when cultivated in the presence of the new fusion protein vs. silk alone. The present work demonstrates the potential of this new fusion protein for future applications in bone regeneration